Key Factors Influencing the Use of Coal Ash as Construction Material in Vietnam - Le, Van Tuan; Le, Hai Yen; Nguyen, Thi Thuy; Nguyen, Thi My Hanh (International Journal of Sustainable Construction Engineering and Technology, 2025)
The accumulation of ash and slag resulting from thermal power plants’s generation poses significant environmental risks to soil, water, and air. The Government of Vietnam has shown particular concern regarding the treatment and management of ash and slag produced by coal-fired power plants. In pursuit of sustainable development goals, the government aims for 80% of the total amount of ash and slag produced by these plants to be reused, recycled, or transfromed into raw materials for manufacturing, building materials, and landfilling while complying with environmental standards. Initial programs and support have been introduced to encourage investors and construction contractors to encourage the utilization of coal combustion ash and slag in construction applications. However, the widespread adoption of ash and slag utilization remains limited due to various challenges including technical, economic, and institutional challenges . This study examines the elements that affect the decision-making processes of construction contractors in Vietnam regarding the use of coal combustion ash and slag as construction materials. Based on prior studies, 18 influencing factors were identified and categorized into five groups. Data were collected from 42 construction contractors. The Fuzzy Analytic Hierarchy Process (FAHP) method was employed to assess the relative importance of these factors in influencing contractors’ decisions. The findings reveal that the most influential factors include: government support programs and policies; unit prices and technical-economic norms of ash and slag; physical properties of ash and slag; financial advantages of utilizing ash and slag as building materials in construction; environmental assurance; and technological innovation.